Politicized celebrities against far-right on Twitter. Political preferences and activity of users retweeting Rosalia’s anti Vox tweet after the 2019 general elections in Spain - Frederic Guerrero-Solé; Eva Pujadas; Toni Aira; Lluís Mas-Manchón (Revista Mediterránea de Comunicación)
Celebrities use social networks to interact with and to mobilize their audiences (Zilinsky, Vaccari, Nagler & Tucker, 2019). Politicized celebrities may assume the role of leaders to counter politicians’ monopoly of political representation and to bring social awareness to specific causes (Street, 2004; Wheeler, 2013). This paper analyzes the impact of politicized celebrities in Twitter among politicized and non-politicized audiences. We focus on the case of the Catalan singer Rosalia, who published a short explicit tweet against the Spanish far-right populist party Vox with the text ‘Fuck vox’ the day after the Spanish general elections in November 2019. We measure the political preferences and activity of Rosalia’s followers, Fuck vox post’s retweeters, and users who retweeted the singer before and after the tweet. The results show that Rosalia had a great impact among left-wing and Catalan separatist parties, and among those users with no political preferences or political activity. In addition, we found that Rosalia’s followers were less likely to be politically active (Loader, Vromen & Xenos, 2016). This study sheds light on the potential of politicized celebrities to mobilize their non-politicized audiences to counter far-right movements in social networks.